Comparison of Methods for the Determination of Formaldehyde in Air. (2nd July 2016) - Giesen, Ruth; Schripp, Tobias; Markewitz, Doreen; Meyer, Bettina; Schwab, Harald; Uhde, Erik; Salthammer, Tunga
ABSTRACT: Different methods have been used for the determination of the amount of formaldehyde present in the air. The Hantzsch method uses derivatization with acetyl acetone, and the fluorescence signal of the resulting chromophore is highly selective for formaldehyde. The 2, 4-dinitrophenylhydrazine procedure allows measuring of carbonyl compounds in combination with high-performance liquid chromatography. In contrast, the 3-methyl-2-benzothiazolonehydrazone method delivers the sum of aliphatic aldehydes, although it is reported to be selective for formaldehyde. To compare the performance of these methods, 13 samples of wooden furniture were measured. Further characterization was performed with a formaldehyde source and one oriented-strand board. As expected, the results of the 2, 4-dinitrophenylhydrazine and Hantzsch methods provided excellent correlation. However, the formaldehyde concentrations obtained from the 3-methyl-2-benzothiazolonehydrazone method showed almost no correlation with the 2, 4-dinitrophenylhydrazine and Hantzsch values. The results demonstrated that there was significant error in calculation with the use of the 3-methyl-2-benzothiazolonehydrazone method for determining the presence of a specific aliphatic aldehyde in a mixture of volatile organic compounds in the air. In addition, emission tests of an artificial formaldehyde source revealed excessively high concentrations of formaldehyde with the 3-methyl-2-benzothiazolonehydrazone method. Therefore, it was found that the 3-methyl-2-benzothiazolonehydrazone method was not suitable for the determination of the presence of formaldehyde in the air due to interferences of other organic compounds and systematic analytical artifacts.